PENERAPAN STRATEGI TANDUR ( TUMBUHKAN, ALAMI, NAMAI, DEMONSTRASIKAN, ULANGI DAN RAYAKAN ) BERVISI SETS ( SCIENCE, ENVIRONMENT, TECHNOLOGY AND SOCIETY ) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PADA POKOK BAHASAN KEANEKARAGAMAN MAKHLUK HIDUP PADA S - Anik Hamidatul Fitria Hamidatul Fitria; Zainul Munawwir (STKIP PGRI SITUBONDO, 2016)
One of the causes of poor quality of teaching biology because of the lack of blend with natural surroundings is a major study of the biology of learning, as well as lack of information and discussion to students in relation to science, environment, technology and society. Students are dreaming of learning to understand the material so it seemed boring. Recognizing the need to find a learning strategy that can support the learning process fun, mingle with nature and understand the benefits to everyday life so as to improve students' motivation as well as ease of understanding in learning biology. Thus it also would improve learning outcomes for students are satisfactory. This study describes a learning strategy TANDUR (Grow, Natural, Named, Demonstrate, and Celebrate Repeat) vision SETS (Science, Environment, Technology and Society) with the goal of improving student learning outcomes class VII-E of Jangkar Junior High Scholl semester at subject diversity of living things. The research was conducted at Jangkar Junior High Scholl, Jangkar Kabuaten Situbondo. The research approach used is qualitative research with classroom action research. Data collection procedures include observation, interviews, documentation and testing. The results showed that the learning strategy TANDUR (Grow, Natural, Named, Demonstrate, Repeat and Celebrate) vision SETS (Science, Environment, Technology and Society) to improve student learning outcomes. Learning outcomes are known from scores obtained by the percentage of students in the classical student mastery of 92.31% and a mean score of 80 rats grade students. This is because student activity pembelaran better follow the strategy used by the researchers. Based on these results it can be suggested that the learning strategy TANDUR (Grow, Natural, Named, Demonstrate, Repeat and Celebrate) vision SETS (Science, Environment, Technology and Society) is used as an alternative approach to sorting out the learning.